Impact of state weights on national vaccination coverage estimates from household surveys in Nigeria. Issue 32 (6th July 2020) - Dong, Tracy Qi; Rhoda, Dale A.; Mercer, Laina D.
Highlights: Nigeria's national survey estimates of DPT3 and MCV1 coverage fluctuate greatly in recent years. Much of the variation results from differences in surveys weights, not coverage. Both USAID DHS and UNICEF MICS allow weights to vary from round-to-round. Nigeria's National Nutrition & Health Survey weights do not vary much due to post-stratification. To compare results from surveys proximate in time, use similar strata weights for clarity. Abstract: National vaccination coverage estimates from household surveys are widely used in monitoring and planning of immunization programs. In Nigeria, survey-reported national coverage estimates have shown large fluctuations in the past few years. In this paper, we examine the impact of state-level survey weighting on Nigeria's national vaccination coverage estimation. In particular, we focus three vaccination-related outcomes among children aged 12–23 months: the coverage of the third dose of diphtheria, pertussis, and tetanus vaccine (DPT3); the coverage of the first dose of measles-containing vaccine (MCV1); and the availability rate of home-based vaccination record (HBR). We compare the sample selection and weight assignment of three major survey programs in Nigeria, and show that considerable portions of the changes in survey-reported national coverage estimates can be explained by shifts in state-level weights. Our analysis demonstrates the importance of state weighting method in estimating aggregated national coverage figures and provides important context for interpreting changes in coverage estimates between surveys in the future.